Overview of Motor Nerve Damage in People with Diabetes Mellitus - Ana Nistiandani; Rondhianto Rondhianto; Muhammad Fakhrur Rozsy (Nursing and Health Sciences Journal (NHSJ), 2021)
Damage to motor nerves in people with diabetes increases the risk of a foot injury. This occurs because the damage results in changes in foot biomechanics, muscle atrophy, deformity, and increased pressure on the feet. So far, the examination of motor nerve damage in people with diabetes in agricultural areas such as the Jember Regency is still rarely touched by primary health services. The purpose of this study was to identify motor nerve damage in people with diabetes in the agriculture area of ​​the Jember Regency. This type of research is exploratory, descriptive, 102 respondents obtained by purposive sampling technique. Inclusion criteria in this study are age> 18 years; do not have DFU active, and did not experience amputation in both legs. Data collection uses instrument modification from MNSI (Michigan Neuropathy Screening Instrument) and MDNS (Michigan Diabetic Neuropathy Score). MNSI using in inspecting for deformity, while MDNS using for forms of physiological reflex damage and muscle strength. The analysis used in univariate and displayed in the frequency distribution. The results showed that the majority of respondents who suffer from DM are experienced in the middle adulthood category (71.6%), with a length of suffering more than five years (95.1%), and have a history of comorbidities (68.6%). The most common form of motor deformity damage was hallux valgus on the right and left legs (38.2%; 26.4%). Forms of motor damage in the form of muscle strength, severe damage to the abduction of the right and left legs (7.8%), and were found right or left toe extensions (1.9%; 2.9%). Motor damage in the form of no physiological reflexes was found in the right and left Quadriceps femoral (2%; 1%), and right or left leg Achilles (1%). The result of total motor damage assessment is that people with diabetes have decreased muscle strength in the right and left extremities (74.5%; 72.5%). This research shows that the majority of people with diabetes in the agricultur area of ​​the Jember Regency suffer motor nerve damage. Therefore, there is a need for preventive measures to prevent the worsening condition of people with diabetes.